Association of Serum Creatinine With Abnormal Hemodynamics and Mortality in Pulmonary Arterial Hypertension - Sanjiv J. Shah; Thenappan Thenappan; Stuart Rich; Lu Tian; Stephen L. Archer; Mardi Gomberg‐Maitland (2008)
Renal dysfunction predicts mortality in patients with cardiovascular disease. How renal dysfunction relates to hemodynamics and mortality in pulmonary arterial hypertension (PAH) remains unclear.We performed a cohort study of 500 patients with World Health Organization group I PAH from 1982 to 2006 with data on demographics, comorbidities, medications, functional class, laboratory tests, exercise testing results, and hemodynamics. Serum creatinine (SCr) was determined on entry into the study (initial PAH clinic visit). Vital status was determined from hospital records and the Social Security Death Index. We used a Cox proportional hazards analysis to determine whether SCr was an independent predictor of mortality. Mean age on entry into the study was 48+/-14 years, and 79% of subjects were female. Mean SCr was 1.05+/-0.35 mg/dL. Elevated SCr was associated with higher right atrial pressure and lower cardiac index. During a median follow-up of 3.5 years, 279 deaths (55.8% of the cohort) occurred. Compared with patients with SCr <1.0 mg/dL, those with SCr 1.0 to 1.4 mg/dL and SCr >1.4 mg/dL had an increased hazard ratio of death (unadjusted hazard ratio 1.65, 95% confidence interval 1.26 to 2.17, P<0.0001 for SCr 1.0 to 1.4 mg/dL; unadjusted hazard ratio 2.54, 95% confidence interval 1.73 to 3.71, P<0.0001 for SCr >1.4 mg/dL). On multivariable analysis, we found a significant interaction between SCr and right atrial pressures (interaction P<0.0001); increased SCr best predicted death in patients with right atrial pressure <10 mm Hg.Renal dysfunction is associated with a worse hemodynamic profile and is an independent predictor of mortality in PAH. Measurement of SCr is practical and offers a simple way to noninvasively predict outcome.